(untitled) (Biological Sciences - PJSIR, 2006)
Colour stability of the versatile annatto dye was examined to monitor the effects of base media on industrial products. The dye was incorporated in two media, namely, palm kernel oil used in products such as body cream and soap, and paraffin wax used in shoe polish and household candle wax. These products were exposed to various light conditions for a specific period before assessment. The melting point of the dye was determined as176-178 °C with a molar absorp- tivity of 13,600 l mol-1 cm-1 at 545 nm. It imparted its brilliant yellow/orange colouration in industrial products as the colour stability depends on the compounding base media of the products. Losses of b-carotene was higher and faster in non- aqueous environment as paraffin wax showed low fastness rating values, than in the palm kernel oil based aqueous medium products.